Cavamax W7 composite psoralen ethosomal gel versus cavamax W7 psoralen solid complex gel for topical delivery: A comparative evaluation - Kumari, Smriti; Pathak, Kamla (International Journal of Pharmaceutical Investigation)
Aim: The present research work was aimed to formulate and characterize psoralen-encapsulated cavamax W7 composite ethosomal gel and compare its in vitro and ex vivo behavior against psoralen-cavamax W7-complex reference gel. Materials and Methods: A total of nine formulations of composite ethosomes were prepared by injection method using 32 factorial design and entrapment efficiency was designated as dependent variable. Concomitantly, psoralen was complexed with cavamax W7 (1:1 molar ratio) by kneading method and formation of complex was confirmed by Diffuse reflectance spectroscopy (DRS), scanning electron microscopy (SEM), X-ray diffraction (XRD), and differential scanning calorimetry (DSC). Results: F9 with vesicle size of 183 ± 2.8 nm, and highest % entrapment efficiency of 98.12 ± 1.15 was selected as optimized formulation. Transmission electron microscopy (TEM) revealed uniform and spherical shaped vesicles. The optimized formulation F9 was formulated as carbapol gel and compared against ethosomal gel, psoralen gel, and psoralen cavamax W7 complex gel. The gels were evaluated for permeation characteristics and the rank order was composite ethosomal gel > ethosomal gel > psoralen-cavamax W7 complex gel > psoralen gel. The ethosomal gel (G5) with highest in vitro permeation of 82.48 ± 2.23% was subjected to in vivo Confocal laser scanning microscopy (CLSM) studies using rhodamine B as tracer. The penetration of rhodamine B was uniform, deeper, and two times faster into epidermis than control gel. Conclusion: Conclusively, cavamax W7 composite ethosomes present themselves as efficient carrier for superior topical delivery of psoralen and have potential for clinical applications in minimizing side effects associated with photosensitivity of psoralen.
Keywords: Composite ethosomes; confocal laser scanning microscopy; permeation; psoralen; psoralen-cavamax W7-complex